Wounded Healers: A Crisis of Violence Against Doctors in Nepal - Banskota, Bibek (Nepal Orthopaedic Association Journal, 2025)
The white coat, once a symbol of trust and healing, has been increasingly under attack by a disturbing surge of violence against doctors and healthcare professionals in Nepal. This alarming trend not only jeopardizes the medical professionals’ well-being, but also the nation’s healthcare system. This editorial explores the escalating trends in such acts of violence, its possible causes, the inadequacies in existing preventive regulations, and the urgent need for comprehensive reform to ensure both the patients and doctors wellbeing.